First Nations’ Women in the Academy: Disrupting and Displacing the White Male Gaze - O'Sullivan, Sandy (Palgrave Macmillan, 2019)
Across colonised countries, the academy has been an instrument of the state and has collaborated in the project of colonial suppression of First Nations’ Communities and Peoples. This inculcation, while compounded for First Nations’ women academics, is being challenged to create a space that disrupts the dominant scrutiny and expectation; our women are leading the change. The chapter aims to provide a roadmap of current practice, contributions, and speculates on potential strategies across research, teaching and engagement in the academy that transform how and why First Nations’ women are achieving through disruption and the displacement of power in the academy.